Case Report: Treating one autoimmune disease induces another: the paradox of TNF-alpha inhibitor therapies - Gehrke, Miranda; Thurau, Stephan; Wildner, Gerhild (Frontiers in Immunology, 2025)
Although TNF-α-blockade is an approved treatment for several autoimmune diseases there are cases of paradoxical induction of autoimmunity appearing under anti-TNF therapy, even of diseases that are usually treated with TNF-blockers. The case of a patient with hidradenitis suppurativa (HS) from the department of dermatology was referred to our eye hospital due to blurred vision and subsequently diagnosed Vogt-Koyanagi-Harada-like disease (VKHLD) as an adverse effect of her long-term adalimumab therapy. A novel antibody targeting IL-17, bimekizumab, was introduced as a therapy for her skin disease with concomitant improvement of her ocular symptoms. In contrast to formerly tested anti-IL-17-antibodies with moderate therapeutic effect on uveitis this novel antibody targets both, IL-17A and -F and is thus expected to be more effective. This case inspired us to further analyze the paradoxical immune mechanisms of TNF-α blockade that might induce autoimmunity and the pathomechanisms of HS and VKHD, revealing an interplay of TNF-α and IL-17 signaling pathways. This led us to a hypothesis explaining the paradox of inducing autoimmunity by TNF-blockade in context with IL-17-mediated autoimmune diseases and an explanation why VKHD should be treated with anti-IL-17A/F rather than with anti-TNF-α.